Place attachment, place satisfaction and pro-environmental behaviour: a comparative assessment of multiple regression and structural equation modelling - Ramkissoon, Haywantee; Weiler, B.; Smith, L. (Routledge, 2015)
Using data collected from 452 visitors at the Dandenong Ranges National Park, Australia, this paper applies multiple regression (MR) and structural equation modelling (SEM) approaches to test the relationships between the respective sub-constructs of place attachment (place dependence, place identity, place affect, place social bonding), place satisfaction, and visitors’ pro-environmental behavioural intentions. Findings revealed differences in strength and magnitude of the regression paths. The SEM analysis further reveals insignificant regression paths between place identity and place satisfaction, and place social bonding and low-effort pro-environmental behavioural intentions in contrast to the MR results. An empirical comparison of the MR and SEM results is expected to shed light on the application of these two powerful techniques in tourism research.